Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1111/j.1600-051x.1978.tb01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetracycline and/or scaling on human periodontal disease

Abstract: Twelve adult patients with severe chronic periodontitis were examined prior to treatment, and after 8 and 25 weeks following tbe start of treatment. Six subjects received tetracycline during weeks 1 and 2 and weeks 7 and 8, while the other six did not. All subjects were instructed in oral hygiene and received a series of scaling and root planing treatments on one side only of their dentition. The contralateral side received no scalings at any time. The experiment was designed to provide clinical and microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
125
0
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(144 citation statements)
references
References 31 publications
13
125
0
2
Order By: Relevance
“…The latter finding suggests that there is no significant difference in PD reduction between mechanical treatment alone and mechanical treatment combined with doxycycline. These findings are consistent with the findings of several previous studies in which no significant difference could be found between mechanical treatment combined with tetracycline or minocycline and mechanical treatment alone (10,11,16). However, contrary findings have also been reported.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The latter finding suggests that there is no significant difference in PD reduction between mechanical treatment alone and mechanical treatment combined with doxycycline. These findings are consistent with the findings of several previous studies in which no significant difference could be found between mechanical treatment combined with tetracycline or minocycline and mechanical treatment alone (10,11,16). However, contrary findings have also been reported.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies on clinical effects of both systemic and local tetracyclines have been performed. In some of these studies, tetracyclines made no statistically significant difference on probing depths and clinical attachment levels (10,11,(14)(15)(16)(17)(18)(19) while in others successful clinical results were obtained by tetracycline and minocycline treatments (20)(21)(22)(23)(24)(25)(26)(27)(28). These studies evaluated only systemic or local antibiotic treatments with or without mechanical periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that an increase in the severity of gingivitis is accompanied by an increase in the percentage of spirochetes in the bacterial plaque [8,16,18]. Following periodontal therapy, an increase in coccoid bacteria and a decrease in spirochetes and motile rods has been observed [19][20][21]. It has also been suggested that subjects with treated periodontitis, with elevated levels of spirochetes and/or motile rods, have more frequent localized recurrences of periodontitis than patients with low proportions of these morphotypes [16].…”
Section: Discussionmentioning
confidence: 89%
“…However, drawbacks such as severe side-effects, bacterial resistance (Olsvik, 1991), and poor local concentrations of antimicrobials have limited this route of administration (Loesche, 1996;Slots & Pallasch, 1996;Vandekerckhove et al, 1997). Systemic antibiotic therapy over a long period of time also raises the risk of undesirable side-effects such as nausea, diarrhea, fever, abdominal pain, and pseudomembranous colitis (Listgarten et al, 1978;Slots et al, 1979;Lindhe et al, 1983). Systemic use of antibiotics has been recently reviewed and it was concluded that the evidencebased literature supports the use of systemic antibiotic therapy for refractory and recurrent periodontitis (Ellen & McCulloch, 1996).…”
Section: Introductionmentioning
confidence: 99%